ALTERNATIF PANGAN KELUARGA MELALUI BUDIDAYA IKAN DAN TANAMAN DALAM EMBER (BUDIKDAMBER) DI KELURAHAN PANANCANGAN - Yeni Widyastuti; Exel Muhammad Rizki; Saka Wilbiharto; Muhammad Rauf; Qin Palapa; Rahmida Sellina; Syafita Maharani (LPPM Universitas Bina Bangsa, 2022)
This community services aim to create an alternative to fulfill family food and nutritional need by optimization limited space that available and it is located in Kelurahan Panancangan, Kecamatan Cipocok Jaya, Kota Serang. The method used in this community service activity is sozialization (offline and online using guidance video from YouTube) and also Q and A method, but with the limited number of participants and implementing the stricted health protocol during the COVID-19 pandemic situation. The result of this community services activity is creativity in food cultivation, food diversityand nutrisious of family consumption in order to maintain our body’s immunity, so that all family members remain healthy, creative and productive during COVID-19 pandemic situation